ESTUDOS DA CONCENTRAÇÃO E DA MOBILIDADE DOS ELEMENTOS METÁLICOS NAS CINZAS DA USINA TERMOELÉTRICA DE CANDIOTA - Sanchez, J. C. D.; Teixeira, E. C.; Fernandes, I. D.; Pestana, M. H. D.; Machado, R. P. (Geochimica Brasiliensis, 2011)